Persamaan Empiris Sifat Mekanika Bambu Wulung - Oka, Gusti Made (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2015)
The development of the use of bamboo increased as non-wood material. The bamboo Gigantchloaatroviolacea is the most popular bamboo used as a construction material in some region of Indonesia.  Some  bamboo weakness are bamboo is a non-homogen material, it has non prismatic sectional form, the stems straigthness is not the same, node on the stems  and a hollow inner cross section. Effects of node, internode and the stem position on  mechanical properties of bamboo were evaluated.  In this article, the mechanical properties of Gigantochloaatroviolacea bamboo was studied (shear strength, compression and tensile and elastic modulus). In this study, the  mechanical properties of bamboo, located at different height were investigated with ISO 22157 and ASTM. The mechanical properties of bamboo at node, internode and height position were tested  in air dry condition. Base on the test results of all properties strength were increased from bottom to top. An empirical equations ware determined base on spesific gravity parameter. Base on its spesific gravity the mechanical properties of bamboocan be determined.